Characteristics of the severely impaired hand in survivors of stroke with chronic impairments. Issue 3 (3rd April 2022) - Barry, Alexander J.; Kamper, Derek G.; Stoykov, Mary Ellen; Triandafilou, Kristen; Roth, Elliot
ABSTRACT: Background: Diminished sensorimotor control of the hand is one of the most common outcomes following stroke. This hand impairment substantially impacts overall function and quality of life; standard therapy often results in limited improvement. Mechanisms of dysfunction of the severely impaired post-stroke hand are still incompletely understood, thereby impeding the development of new targeted treatments. Objective: To identify and determine potential relationships among the mechanisms responsible for hand impairment following stroke Methods: This cohort study observed stroke survivors (n = 95) with severe, chronic hand impairment (Chedoke-McMaster Hand score = 2–3). Custom instrumentation created precise perturbations and measured kinematic responses. Muscle activation was recorded through electromyography. Strength, spasticity, muscle relaxation time, and muscle coactivation were quantified. Results: Maximum grip strength in the paretic hand was only 12% of that achieved by the nonparetic hand, and only 6 of 95 participants were able to produce any net extension force. Despite force deficits, spastic reflex response of the finger flexor evoked by imposed stretch averaged 90.1 ± 26.8% of maximum voluntary activation, relaxation time averaged 3.8 ± 0.8 seconds, and coactivation during voluntary extension exceeded 30% of maximum contraction, thereby resulting in substantial net flexion. Surprisingly, these hypertonicity measures were not significantly correlated with each other. Conclusions: Survivors of severe, chronic hemiparetic stroke experience profound weakness of both flexion and extension that arises from increased involuntary antagonist activation and decreased voluntary activation. The lack of correlation amongst hypertonicity measures suggests that these phenomena may arise from multiple, potentially independent mechanisms that could require different treatments.